A Comparative Study of Methods for Obtaining Silicon Carbide Ceramic Materials - Belyakov, A. N.; Markov, M. A.; Dyuskina, D. A.; Bykova, A. D.; Chekuryaev, A. G.; Kashtanov, A. D. (Refractories and industrial ceramics, 2023)
To date, about ten different methods for producing silicon carbide ceramic materials have been developed. This study presents the mechanisms and describes the advantages and disadvantages of the most commonly used methods for forming and sintering SiC powders. The article describes the basic properties and the application areas of resulting ceramic articles.